A Study on Unemployment rate of Youth Graduates Student in Malaysia - Gan, Kia Hui; Teoh, Kok Ban; Cheah, Zong Bin; Teh, Wan Xin; Tan, Qing Yee; Ng, Ningze; Goh, Yi Lin; Prerna, Kumari; Kanoujiya, Snehal Deepak (Journal of The Community Development in Asia, 2024)
This research aims to investigate how English Proficiency, Employability Skills and Job Mismatch affect unemployment rate among youth graduate students. This quantitative research distributed an online questionnaire to collect data from 300 unemployed youth graduate students. The findings concluded that  English proficiency and job mismatch  have significant positive relationship with unemployment rate, whereas employability skills possess a significant negative relationship with unemployment rate. The findings contribute to the continuous improvement on unemployment rate among the youth graduate students of Malaysia by English proficiency, employability skills and job mismatch.